Sabolović-Krajina, Dijana. Narodne knjižnice u tranziciji: sociološki aspekti - Ivana Sabljak (Vjesnik Bibliotekara Hrvatske, 2021)
Sabolović-Krajina, Dijana. Narodne knjižnice u tranziciji: sociološki aspekti. Koprivnica: Meridijani, 2020. 304 str. ISBN 9789532392364